An IoT Multi-Protocol Strategy for the Interoperability of Distinct Communication Protocols applied toWeb of Things - Barros, Vinícius A.; B. Junior, Sérgio A.; Bruschi, Sarita M.; Monaco, Francisco J.; Estrella, Júlio C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2019: Proceedings of the 25th Brazilian Symposium on Multimedia and the Web, 2019)
In 2020, fifty billion devices will be part of the global computer network. This expectation has raised several discussions and challenges on the heterogeneity of hardware and software on the Internet of Things (IoT). Interoperability is one of the main challenges and it consists of the integration of heterogeneous devices and services. Recently, the Web of Things (WoT) concept emerged as new way to provide IoT services as web resources, which enables the integration of heterogeneous technologies. This paper introduces a multi-protocol strategy for the interoperability of distinct communication protocols (HTTP, MQTT, and CoAP) applied to Web of Things context and it reports a set of experiments with different workloads and evaluation scenarios. The contributions include the performance of the multi-protocol strategy and the bottlenecks analysis of the evaluated protocols. The results show the response time variation when using Machine-to-Machine (M2M) devices (Raspberry Pi and ESP8266) and a cloud-based environment and the better performance of CoAP and MQTT in comparison to HTTP.